Does Zakat Disclosures as Corporate Social Responsibility (CSR) Have an Impact on Islamic Banking Performance? - Aam Slamet Rusydiana; Ririn Riani (International Journal of Zakat, 2022)
This study aims to examine the impact of zakat disclosure, especially on the application of corporate social responsibility (CSR) which is the contribution of Islamic banking to its financial performance, namely return on assets and return on equity. This study focuses on 8 Islamic commercial banks in Indonesia from 2011 to 2020. The sample was selected based on the transparency regarding zakat disclosure in their annual report. The method in this study uses a panel data approach. The results show that the contribution of zakat disclosure as corporate social responsibility has a positive and significant effect on both models of Islamic bank financial performance in Indonesia. This shows that CSR through zakat can support the stakeholder theory where Islamic banks that focus on social obligations will improve their financial performance. This study provides a theoretical contribution by explaining disclosure of zakat is an obligation for Islamic banks, and provides important empirical evidence for policy implications. Thus, Islamic bank management may find the importance of CSR in zakat disclosure through reports on sources of funds and distribution of zakat funds in their financial statements for the benefit of stakeholders.